PENENTUAN PORTOFOLIO OPTIMAL SAHAM PERUSAHAAN MANUFAKTUR SEBAGAI DASAR PENENTAPAN INVESTASI SAHAM - Ni Kadek Susi Listiari; Sang Ayu Putu Arie Indraswarawati (Hita Akuntansi dan Keuangan, 2020)
TheZpurpose ofPan investor in investing is to get the maximum return on their shares. However, various problems arise because of the many stock investment instruments circulating in the capital market. The population have been usedXin this study are all manufacturing companiesRwhichTareOclassified as LQ-45 shares, as many as 15 companies. The methodPofPdeterminingTtheXsample using a purposive sampling technique. The sample used in this study is manufacturing companies that have passed all the criteria, which are 13 companies or 156 samples. The dataPanalysis technique used is descriptive quantitative analysis, which is analyzing the formation of an optimal portfolio with the Single Index Model. Based onHtheUresults, the CSPI data used to represent market data has an expectedOmarket returnPof -0.00038159 or 0.038% per month and a standard deviation of 0.03322 or 3.32%. While the market risk is 0.00110399 or 0.11%. There are 7 stocks that meet the criteria become candidates for the formation of an optimal portfolio, because the ERB value of each share is greater than the value of each cut off rate (Ci). Whereas there are 6 ERB shares which have value smaller than Ci, not included in the optimal portfolio candidate.